Readiness Digital Mengatasi Cyber War: Studi Kasus tentang Cyber War Indonesia dan Australia - Herlina; Yeby Ma’asan Mayrudin; Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2024)
This paper aims to examine the issue of digital readiness in overcoming cyber war between Indonesia and Australia. The existence of cyber conflict has given rise to an evaluation for the government to continue to improve the security system. The wiretapping carried out by the Australian government was a presumptuous act and the Indonesian government and the public condemned the act. The wiretapping action triggered a cyber war between Indonesia and Australia. This research method uses a qualitative Creswell case study approach that focuses on analyzing a case. The theory used is Game Theory and Cyber Conflict. The results of the study show that the cyber war that occurred between Indonesia and Australia can be concluded: First, the conflict that occurred involved government and community actors. Second, if the cyber war is won by one party will get a little benefit then negotiations are taken to get a lot of benefits. Third, the resolution of the cyber war between Indonesia and Australia is to sign an agreement and re-establish bilateral relations. To strengthen cyber security, qualified digital readiness is needed, so cooperation is needed to create such a thing.